Modern Property Marketing Strategy: Combining Conventional and Digital Approaches - Meri Linawati Tanuwidjaja (Return : Study of Management, Economic and Bussines, 2025)
Property marketing today requires a more adaptive approach as digital technology develops. Although many companies are starting to combine conventional and digital marketing strategies, there is still a gap in the understanding of how this integration can be done effectively. This study aims to explore the application of a combination of conventional and digital marketing strategies in the property industry and to identify the challenges faced in its implementation. This study uses a qualitative approach by conducting in-depth interviews with 5-10 participants who have more than three years of experience in the property industry. Data is collected to analyze the advantages and disadvantages of each approach. The results showed that conventional marketing, such as brochures and exhibitions, is effective in reaching local audiences and building personal relationships, but has limitations in reaching a wider market. In contrast, digital marketing allows access to a larger audience and efficiency in measuring results. The combination of these two approaches provides competitive advantages, such as increased market reach and lead conversion. The main challenges faced in this integration include the high cost of conventional marketing, the difficulty of maintaining message consistency, and the need for more resources to manage both strategies simultaneously. This study concludes that the integration of conventional and digital marketing can provide a more holistic and effective solution in facing competition in the property industry. By utilizing the strengths of both approaches, property companies can achieve optimal marketing results and increase competitiveness in an increasingly complex market.